Historische Wirtschaftskarte der Rheinlande um 1820. Regierungsbezirk Düsseldorf-Kleve - Hahn, Helmut; Krings, Wilfried; Zorn, Wolfgang (ERDKUNDE, 1970)
Since the preliminary report in Erdkunde XXI/3/1967, it has been possible, through co-operation between economic geographers and economic historians, to complete the collection of material for the Economic Map of the Rhine lands (1820). Because the cartographic portrayal of the collected material at a scale of 1 : 200 000 compels selectivity, the publication of the complete map is being preceded by a sample sheet. The choice fell on the Administrative District (Regierungsbezirk) of Düsseldorf as an early centre of the Rhineland economy. This article is intended to give an indication of the text which will accompany the complete map and discusses three subject areas: land use, agriculture and industrial production. At the same time it attempts to provide an introduction to the linkages between these subject areas and gives information on sources and the general political and economic conditions of the time. Because cartographic feasibility - let alone the often unsatisfactory sources - did not permit presentation of goods movements, textual sketches touch on these. The authors would be grateful for any criticism and suggestions, in the knowledge that the man presented here can only be a first attempt.